Il City Information Modeling (CIM) nelle piattaforme decisionali urbane - Carlucci, Renzo (GEOmedia, 2022)
To evaluate how the CIM contributes to improving public services and the quality of life of citizens, studies conducted by some authors have analyzed the international standard ISO 37120 - Sustainable cities and communities - Indicators for city services and quality of life and City Information Modeling (CIM) data that can be used to obtain useful data for ISO indicators 37120. The CIM paradigm, understood as an approach to a global model of the city, must absolutely be formed by the incorporation of BIM models of buildings that have a geographical insertion in the reference system in use. In this way all the data relating to the cities will be available and attached to the georeferenced representations of the buildings present in the CIM database.